The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0075867
|View full text |Cite
|
Sign up to set email alerts
|

Cell Wall Degrading Enzyme Induced Rice Innate Immune Responses Are Suppressed by the Type 3 Secretion System Effectors XopN, XopQ, XopX and XopZ of Xanthomonas oryzae pv. oryzae

Abstract: Innate immune responses are induced in plants and animals through perception of Damage Associated Molecular Patterns. These immune responses are suppressed by pathogens during infection. A number of studies have focussed on identifying functions of plant pathogenic bacteria that are involved in suppression of Pathogen Associated Molecular Pattern induced immune responses. In comparison, there is very little information on functions used by plant pathogens to suppress Damage Associated Molecular Pattern induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
58
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 54 publications
2
58
0
Order By: Relevance
“…Thus, it is possible this protein is associated with host cell membranes following secretion. Our observations for XopK are contrasted with the roles of AvrBs2 and XopX, which exhibit reduced virulence phenotypes, consistent with previous studies (Kearney and Staskawicz, 1990;Metz et al, 2005;Zhao et al, 2011;Sinha et al, 2013;Li et al, 2015b;Stork et al, 2015). Our results further illustrate that T3E mutants may impact certain aspects of host-pathogen interactions more than others.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, it is possible this protein is associated with host cell membranes following secretion. Our observations for XopK are contrasted with the roles of AvrBs2 and XopX, which exhibit reduced virulence phenotypes, consistent with previous studies (Kearney and Staskawicz, 1990;Metz et al, 2005;Zhao et al, 2011;Sinha et al, 2013;Li et al, 2015b;Stork et al, 2015). Our results further illustrate that T3E mutants may impact certain aspects of host-pathogen interactions more than others.…”
Section: Discussionsupporting
confidence: 91%
“…AvrBs2 contains a glycerol phosphodiesterase domain that is required for its virulence functions in other Xanthomonas pathovars (Kearney and Staskawicz, 1990;Tai et al, 1999;Zhao et al, 2011;Li et al, 2015b). XopX is involved in suppressing pathogen-triggered immunity (Metz et al, 2005;Sinha et al, 2013;Stork et al, 2015). XopK was first identified in the rice pathogen Xanthomonas oryzae pv.…”
mentioning
confidence: 99%
“…Recent studies highlighted that some T3Es may play a role in suppressing both PTI and ETI. For example, in Xe, XopQ suppresses cell death controlled by the ETI-associated MAP (mitogen-activated protein) kinase MAPKKKa in tomato and pepper (130), whereas in Xoo, XopQ was described to suppress DAMP-induced PTI in rice (120). Another example is that of XopB, which suppresses flg22-induced PTI as well as ETI induced by XopG, AvrBsT, and XopJ in Nicotiana benthamiana (116).…”
Section: Type III Effector Proteins As Major Host-specificity Determimentioning
confidence: 99%
“…XopAA Xoo targets OsBAK1, a coreceptor for many PRRs, and OsBRI1, a brassinosteroid receptor, as supported by the observation that transgenic plants expressing XopAA Xoo exhibit a brassinosteroid-insensitive phenotype 21 . In addition, XopN, XopR and XopX also have been shown to suppress host immune responses in plants [22][23][24] 29 . Thus, these recent investigations have revealed that the effectors target key components controlling host immune responses in plants.…”
mentioning
confidence: 99%